SCAFFOLDING INSTRUCTION IN TEACHING HORTATORY EXPOSITION WRITING - Ilham, - (2010)
This study examines the way EFL teachers scaffold their students in the writing instruction and the possible impact of the instruction on the quality of students' work. It is a qualitative case study because it focused on a particular situation (classroom setting) and a specific phenomenon (scaffolding instruction in EFL classroom). This research was conducted at two senior high schools in Cimahi and Cisarua employing multiple data collection techniques, particularly classroom observation, interview and students' text analysis. The results of the present study have revealed four findings. First, there are eleven types of scaffolding instruction used by the teacher on the stage of GBA. Second, the actualization of the scaffolding instructions was mostly provided in Modeling of Text (MoT) and weakens in Independent construction (JCoT) stage. Third, there seems to be relationship between teachers' awareness and realization of scaffolding. Finally, most students have shown a significant progress in terms of social function, schematic structures, and linguistic features. These suggest that instructional scaffolding, to some extents, is proven effective in developing the students' writing capacity of hortatory exposition texts.